Kenya : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2020)
This World Bank Systematic Country Diagnostic (SCD) provides an analytical foundation for identifying country-level actions and investments that would increase growth and boost shared prosperity in Kenya. It aims to be an objective diagnostic that analyzes and prioritizes binding constraints on development, based on government and external sources as well as consultations with local stakeholders. The conceptual framework adopted for this SCD is organized around two main strategies: (1) higher aggregate output and productivity growth and (2) greater equity and inclusiveness. Constraints limiting advancement in these two key thematic areas are identified using the latest available data. The document then outlines three main pathways to accelerate the attainment of the World Bank’s “twin goals” of ending extreme poverty and promoting shared prosperity. Using filtering criteria and with attention to foundational issues that cut across all sectors, this SCD proposes specific priorities for development initiatives in Kenya.